Economic fears of mass migration from southern Italy in early twentieth century America. Issue 1 (1st January 2019) - Fauri, Francesca
ABSTRACT: Economic fears in the early twentieth century America about Italian immigration united trade unions and white collar workers and were motivated by reasons that ranged from the belief that migrants were disrupting the labour market and were temporary opportunist earners, unwilling to integrate and living in isolated communities, to the idea that southern Italians did not offer sufficient human capital: they were mainly illiterate, and had high dropout rates in schools, and were widely believed to have children with mental disabilities. These American fears were wildly overstated, however. First, Southern Italian migrants had to undergo a two-stage positive selection for literacy, while, secondly only 28.4 per cent of the massive incoming flow of Italians decided to stay; most Italian immigrants chose to return to their country of origin and the minority who remained did not delay long to join in the American melting pot.